STAT3 inhibition sensitizes colorectal cancer to chemoradiotherapy in vitro and in vivo. Issue 4 (3rd September 2013) - Spitzner, Melanie; Roesler, Birte; Bielfeld, Christian; Emons, Georg; Gaedcke, Jochen; Wolff, Hendrik A.; Rave‐Fränk, Margret; Kramer, Frank; Beissbarth, Tim; Kitz, Julia; Wienands, Jürgen; Ghadimi, B. Michael; et al.
<x xml:space="preserve">Abstract</x> Increased activity of signal transducer and activator of transcription 3 (STAT3) is common in human malignancies, including colorectal cancers (CRCs). We have recently reported that STAT3 gene expression correlates with resistance of CRC cell lines to 5‐fluorouracil (5‐FU)‐based chemoradiotherapy (CT/RT). This is of considerable clinical importance, because a large proportion of rectal cancers are resistant to preoperative multimodal treatment. To test whether STAT3 contributes to CT/RT‐resistance, we first confirmed that STAT3 protein expression correlated positively with increasing resistance. While STAT3 was not constitutively active, stimulation with interleukin‐6 (IL‐6) resulted in remarkably higher expression levels of phosphorylated STAT3 in CT/RT‐resistant cell lines. A similar result was observed when we determined IL‐6‐induced expression levels of phosphorylated STAT3 following irradiation. Next, STAT3 was inhibited in SW480 and SW837 using siRNA, shRNA and the small‐molecule inhibitor STATTIC. Successful silencing and inhibition of phosphorylation was confirmed using Western blot analysis and a luciferase reporter assay. RNAi‐mediated silencing as well as STATTIC treatment resulted in significantly decreased clonogenic survival following exposure to 3 µM of 5‐FU and irradiation in a dose‐dependent manner, with dose‐modifying factors of 1.3–2.5 at a surviving fraction of 0.37. Finally, STAT3 inhibition led to a profound CT/RT‐sensitization in a subcutaneous xenograft model, with a significantly delayed tumor regrowth in STATTIC‐treated mice compared with control animals. These results highlight a potential role of STAT3 in mediating treatment resistance and provide first proof of concept that STAT3 represents a promising novel molecular target for sensitizing resistant rectal cancers to CT/RT.